PENGARUH PENGALAMAN, RISIKO AUDIT, DAN KEAHLIAN AUDIT TERHADAP PENDETEKSIAN KECURANGAN (FRAUD) OLEH AUDITOR - Nabilah Rafifah Khairunnisa; Cris Kuntadi (LPPM Institut Pendidikan Nusantara Global, 2022)
The large number of fraud cases that have occurred has created new challenges for the external auditor in detecting such fraud. Doing previous research is very important in reviewing an article or scientific journal. The previous research is a reference for an article on solving problems that occur. This article reviews the variables that can affect fraud in the financial statements committed by the auditor. The purpose of this article is to determine the effect of experience, audit risk, and audit expertise on fraud detection by auditors. The method used is literature review or literature review. This type of research is descriptive quantitative. The type of data synthesis used is the narrative method by grouping similar data according to the results measured to answer the objective. The results of the research show that experience, audit risk, and audit expertise simultaneously or jointly have a significant effect on fraud detection by auditors. Partially, each independent variable provides a different conclusion. Partially, audit experience and audit expertise have a significant effect on the detection of fraud (fraud) by the auditor, while audit risk partially has no effect on the detection of fraud (fraud) by the auditor.